Modeling E-Commerce Website Using QFD - Manik Ayu Titisari; Surjo Hadi; Yitno Utomo; Denis Fidita Karya; Gerald Binta Syarifudin Aliansa (UNUSA Press, 2023)
In the last decade, technological developments and advances in the digital economy have changed consumer behavior significantly. In this millennial era, all levels of society can easily use e-Commerce. Meeting customer needs, even exceeding their expectations, is crucial in this intense digital business competition. This study took place at a X Store, which aimed to identify service attributes that would be developed to improve their quality. This study used the Quality Function Deployment (QFD) method, which began with surveys and interviews, then distributed questionnaires to respondents (customers) to find the Voice of Customers, and then processed the data using QFD. The results showed that: 1) the attribute Product Quality had the highest level of importance, with an importance level of 4.63; 2) the attribute Complete Product Type had the top priority for superior performance, with a weight value of 4.6398; 3) the technical response Easy Order Tracking Service is a top priority for improvement, with a priority value of 6.3224 and a normalized contribution of 32.44%.